Producing content to direct attention traffic along the information superhighway computational marketing communication of SEO in the Philippines - Payabyab, May Gordoncillo 1986- (2018)
"On the internet, search engines hold the keys to creating order out of chaos in the attention economy. This sociocultural study explored the burgeoning industry of Search Engine Optimization or SEO firms, new media's form of advertising and public relations. Quantitative and qualitative methods were used, particularly survey and case studies. The study's primary goal was to empirically understand the nature of 21st century computational marketing communication through the Philippine SEO industry, as existing studies tend to analyze search engines on macroscopic views, such as on historical or philosophical perspectives. This study profiled the SEO industry, analyzed cases in-depth, and drew up a new model of computational marketing communication. This study found that the Philippine SEO industry is in its infancy stage, is technically governed by SEs, and least influenced by social institutions. SEO firms also produced meta-content and articles the most in their campaigns. In conclusion, for new media and the SEO industry to mature, existing and/or new social self-regulatory bodies - together with multi-sectoral and interdisciplinary collaboration - all need to work more aggressively on strengthening new-existing policies, regulatory implementation, and vigilance to make sure that new media professionals, including SEO firms, operate in a culture with balanced interests where social responsibility is prioritized."